Application of multiplication method using multiplication board to elementary school students - Adelya Putri, Barika; Zamhari, Ahmad; Laily, Isyroh; Resti Paramita, Dyah; Furwanti, Elsy (Educenter : Jurnal Ilmiah Pendidikan, 2023)
In order to meet the development of mathematics learning in elementary school children, we find and form media to improve the material to make it easier for students to learn, therefore we create learning media namely "Smart Multiplication Board". which serves to improve teaching methods and facilitate teachers in pedagogy. This research is included in the type of research and development, which is carried out to develop certain products and test the effectiveness of the product. the development example used in this research is the ADDIE development example. Based on the results of observations that have been made during implementation research, students' enthusiasm for using the learning media that has been developed is very good, it can be seen that students are impatient to use learning media. Math Multiplication Smart Board Learning Media on multiplication material is declared feasible to use based on quality assessments from media experts, material experts and learning experts as well as media feasibility from student and teacher responses. The final product of the learning media of the Math Multiplication Smart Board (Panlintarmatika) is a medium that belongs to the type of visual media.